2009
DOI: 10.1007/s11258-009-9711-3
|View full text |Cite
|
Sign up to set email alerts
|

Competitive and allelopathic effects of garlic mustard (Alliaria petiolata) on American ginseng (Panax quinquefolius)

Abstract: The purpose of this study was to test competitive and allelopathic effects of invasive garlic mustard on American ginseng (Panax quinquefolius) seedlings under natural conditions. For comparative purposes, we also examined the potential effects of the native striped violet (Viola striata). In order to partition effects of resource competition and chemical suppression via allelopathy, field soils were amended with activated carbon or left unamended. Activated carbon positively affected ginseng growth as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…A plant species may interfere with other plant species through competition, allelopathy or both. Competition and/or allelopathy in crop–weed interactions occur frequently in cropping systems . Although the relative impacts of allelopathy in crop–weed interactions are still being elucidated, this non‐competitive interference influences the growth and establishment of weeds that may act either independently or synergistically with competition and other interactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A plant species may interfere with other plant species through competition, allelopathy or both. Competition and/or allelopathy in crop–weed interactions occur frequently in cropping systems . Although the relative impacts of allelopathy in crop–weed interactions are still being elucidated, this non‐competitive interference influences the growth and establishment of weeds that may act either independently or synergistically with competition and other interactions.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have shown that the participation of allelopathy, which results from the allelochemicals released from crop varieties themselves, is also a key non‐competitive interference . There is a wealth of information on competitive and allelopathic interference between crop plants and weeds . However, when it comes to the relative impact of allelopathy either independently or synergistically with competitive factors on the growth and establishment of weeds, there is a lack of data, which calls for further studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Garlic mustard reduces native plant germination, growth, and diversity by releasing secondary compounds (allelopathy) that diminish and disrupt mycorrhizal associations, altering soil chemistry, and outcompeting natives for space and resources Meekins and McCarthy, 1999;Stinson et al 2006;Roberts and Anderson, 2001;Prati and Bossdorf, 2004;Murphy 2005;Barto et al, 2010;Cipollini and Gruner, 2007;Stinson et al, 2006;Wolfe et al, 2008;Wixted and McGraw, 2010;Lankau, 2011). Deer could accentuate these impacts to native plants via ''apparent competition'' if deer and other herbivores avoid Alliaria to feed preferentially on native species.…”
Section: Introductionmentioning
confidence: 99%
“…The mere presence of invasives, however, does not demonstrate competitive effect. A follow‐up experimental study compared the effects of planted A. petiolata with that of a planted native species, Viola striata , around target ginseng plants . Alliaria increased seedling mortality, and treatment of soil with activated carbon reduced this effect somewhat, suggesting it may have been due to allelopathy.…”
Section: Interactions With Other Speciesmentioning
confidence: 99%